2018
DOI: 10.1111/1742-6723.13154
|View full text |Cite
|
Sign up to set email alerts
|

Modified Sequential Organ Failure Assessment sepsis score in an emergency department setting: Retrospective assessment of prognostic value

Abstract: For ED patients thought likely to have sepsis, the mSOFA score distinguished those with a high or low mortality risk. The high negative predictive value could be practically useful. Prospective study of the mSOFA score used in ED will be needed to validate these observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
2
20
0
Order By: Relevance
“…Studies with other foci and organ failure definitions have identified in-hospital mortality at 5%–15%9–11 for patients with new organ failure, which is in accordance with our 0–7-day mortality findings. Research on more restricted patient populations in the ED, suspected infection or sepsis patients, has presented in-hospital mortality around 10%, 30-day mortality between 10% and 25% and 1-year mortality around 30%, and in parallel to the present study with mortality increasing by increasing number of organ failures 4 42 43. Furthermore, cerebral failure, as in our study, had the strongest association with short-term mortality, followed by respiratory and circulatory failure, the latter in contrast to our study, and hepatic and cerebral failure were associated with long-term mortality 14.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Studies with other foci and organ failure definitions have identified in-hospital mortality at 5%–15%9–11 for patients with new organ failure, which is in accordance with our 0–7-day mortality findings. Research on more restricted patient populations in the ED, suspected infection or sepsis patients, has presented in-hospital mortality around 10%, 30-day mortality between 10% and 25% and 1-year mortality around 30%, and in parallel to the present study with mortality increasing by increasing number of organ failures 4 42 43. Furthermore, cerebral failure, as in our study, had the strongest association with short-term mortality, followed by respiratory and circulatory failure, the latter in contrast to our study, and hepatic and cerebral failure were associated with long-term mortality 14.…”
Section: Discussionsupporting
confidence: 68%
“…Earlier studies have used, for example, discharge diagnoses, single organ failure scoring system or modified 2001 sepsis consensus organ failure definitions 8–11 51. Recently, most studies present organ failure data based on the SOFA Score,24 25 but some of the values are not clinical applicable to the ED, and this have led to almost equal attempts to modify the SOFA Score to fit the different ED settings in studies conducted 42 52 53. These approaches are almost identical to our modified organ failure definitions, but the circulatory and respiratory differs slightly from study to study due to differences in accessible information in different ED settings.…”
Section: Discussionmentioning
confidence: 99%
“…1 Disruptions to treatment and discontinuation of care potentially result in unexpected visits to EDs. 2 Our study aimed to better understand management of adolescents and young adults (AYAs) with chronic illnesses from an ED clinician's perspective. Face-to-face interviews with a semi-structured questionnaire based on common literature and clinical themes 1,3 (Table 1) were conducted with 20 ED clinicians (medical, nursing, allied health) from one large adult teaching hospital.…”
Section: Transition Care and The Emergency Departmentmentioning
confidence: 99%
“…It was a good exploratory study that highlighted the use of the scoring in an emergency setup as the original SOFA scoring was validated in ICU settings. 2 With the new Sepsis-3 guidelines, 3 there has been a push for early recognition and management of sepsis patients in order to reduce mortality. Before using mSOFA as an emergency tool, we wanted to highlight a few concerns.…”
mentioning
confidence: 99%
See 1 more Smart Citation